How Do Physics Teachers Implement the Merdeka Curriculum in Learning Activities? - Nila Mutia Dewi; Sutarto Sutarto; Ernasari Ernasari; Rangga Alif Faresta (Journal of Education and Teaching (JET), 2025)
The implementation of the Merdeka Curriculum in Indonesia since 2022 has encountered various challenges, particularly in physics learning. This study aims to identify and address these challenges by examining how physics teachers implement the Merdeka Curriculum. Using a qualitative case study approach, data were collected over four months from 14 physics teachers in five high schools in Jember Regency. The study employed interviews, observations, and documentation, analyzed through the Miles and Huberman model: data reduction, data presentation, and conclusion drawing. The findings reveal three key stages in the learning process: introduction, core, and closing. While teachers present objectives and problem orientation in the introductory phase, motivation and initial assessments are lacking. Core activities involve discussions and practicums but are mainly lecture-based, with minimal application of differentiated learning. The closing stage includes reflection, summary, and assignments. However, inconsistencies between observations and interviews indicate the suboptimal implementation of differentiated learning. To enhance curriculum effectiveness, teacher training in lesson planning and formative assessments is essential. This study's limitation is its small participant pool, suggesting future research should expand the sample size for broader validation.